REVEALING AND BUILDING THE PROFESSIONAL COMMITMENT OF AUDITOR THROUGH LOCAL WISDOM PERSPECTIVE OF THE KAILI COMMUNITY - Nur Alimin Azis; Rahayu Indriasari (SEIKO : Journal of Management & Business, 2020)
This study aims to reveal the professional commitment of auditor in local wisdom perspective of the Kaili ethnic community. Qualitative approaches through data reduction and interpretation are used as data analysis. Source triangulation through the case which related to auditor professional commitment was implemented to get a total comprehension. The elaboration result of auditor professional commitment with the local wisdom of Kaili ethnic indicates that auditor professional commitment will be faded by the individual behaviour which are nevadai, nenavusaka, and nebagiu. In contrary, the auditor professional commitment can be maintained if the auditor adheres to the Kaili’s cultural values of local wisdom in doing good that relates to daily life, namely ane mamate rai nembali, pakadoli gau nemo mabali (to always doing good in life, do not bother it with wickedness), ane raja madago, maria rasi (good favor brings many benefits), belo raporia belo rakava (good deeds will be rewarded with good deeds).